2017
DOI: 10.5114/amscd.2017.72535
|View full text |Cite
|
Sign up to set email alerts
|

Expression of beclin-1 and apoptosis-related genes in childhood acute lymphoblastic leukemia

Abstract: Introduction: Autophagy was found to play a major role in the pathogenesis of acute lymphoblastic leukemia (ALL). In this study we investigated the expression of beclin-1, Bad, Bax, Bcl-2, and Bcl-xL in patients with ALL. Material and methods: This was a comparative study conducted on 100 ALL patients (age 8-15) divided into 2 groups. The first group, the ALL group, comprised ALL cases at their initial diagnosis (46 patients), while the second group, the Remission group, comprised in-remission cases (50 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Abdelsalam et al studied the expression levels of a series of autophagic beclin-1, pro-apoptotic (Bad and Bax), and anti-apoptotic (Bcl-2 and Bcl-xL) parameters, illustrating the correlation between their levels in ALL. There was a positive correlation with Bcl-2, while there was a negative correlation with beclin-1 [18].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Abdelsalam et al studied the expression levels of a series of autophagic beclin-1, pro-apoptotic (Bad and Bax), and anti-apoptotic (Bcl-2 and Bcl-xL) parameters, illustrating the correlation between their levels in ALL. There was a positive correlation with Bcl-2, while there was a negative correlation with beclin-1 [18].…”
Section: Discussionmentioning
confidence: 83%
“…In addition to markers of risk such as WBC and age, there is increasing evidence that biomarkers of cellular apoptosis and autophagy, such as beclin-1 and B-cell lymphoma-2 (Bcl-2) levels, may have potential prognostic value in ALL [18]. Autophagy is a catabolic pathway involving degradation of lysosomes and then recycling of cell proteins and organelles [19].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of any of the three aforementioned genes had no significant role with respect to the prognosis of ALL; this finding is consistent with the results of Hogarth and Hall [36] who reported that none of these three proteins had any significant influence on the prognosis and eventfree survival associated with ALL in children. In contrast, Abdelsalam et al [52] reported that the overexpression of BCL2 and BCL-XL had a significant influence on the prognosis and event-free survival associated with ALL in children.…”
Section: In All Patientsmentioning
confidence: 89%
“…Under normal conditions, autophagy prevents ROS accumulation through elimination of damaged mitochondria. However, dysregulation of autophagy may lead to development of tumorigenesis through the accumulation of oncogenic mutations and malignant transformation [30]. Autophagy eliminates damaged or harmful cel-lular components, whereas catalase plays an important protective role by detoxifying ROS [31].…”
Section: Discussionmentioning
confidence: 99%